Focused ultrasound therapy for Alzheimer’s disease: exploring the potential for targeted amyloid disaggregation - Scott, Kurt; Klaus, Stephen P. (Frontiers in Neurology, 2024)
Alzheimer's disease, a progressive neurodegenerative disorder, is marked by beta-amyloid plaque accumulation and cognitive decline. The limited efficacy and significant side effects of anti-amyloid monoclonal antibody therapies have prompted exploration into innovative treatments like focused ultrasound therapy. Focussed ultrasound shows promise as a noninvasive technique for disrupting the blood-brain barrier, potentially enhancing drug delivery directly to the brain and improving the penetration of existing therapeutic agents.This systematic review was conducted using PubMed and Embase databases, focusing on studies published in the last ten years that examined the use of low intensity focused ultrasound for blood brain barrier disruption in Alzheimer's disease. The search strategy encompassed terms related to Alzheimer's disease, focused ultrasound, and the blood-brain barrier. Studies were selected based on predefined inclusion and exclusion criteria. The quality of included studies was assessed using the Oxford Centre for Evidence-Based Medicine Levels of Evidence framework.Twelve studies were analysed, the results of which suggested that low intensity focused ultrasound when combined with microbubbles may safely and transiently disrupt the blood brain barrier. These studies, primarily early-phase and observational, highlight the potential feasibility of focused ultrasound in facilitating drug delivery to the brain for the treatment of Alzheimer's disease. Notably, one study reported positive impacts on cognitive tests, suggesting potential direct therapeutic effects of focused ultrasound beyond blood-brain barrier disruption.The results of the included studies indicate the use of focused ultrasound in Alzheimer's disease treatment might be safe and effective in transiently opening the blood-brain barrier. Although current evidence is promising, further research is needed to establish generalisability. Future studies should also aim to further elucidate the mechanisms of action of low intensity focused ultrasound as well as microbubbles for blood-brain barrier opening and explore potential clinical benefits beyond blood-brain barrier opening such as impacts on cognitive outcomes. Future studies should also aim for greater participant diversity to ensure findings are applicable across the full spectrum of Alzheimer's disease patients.